Clinical features and human T-cell leukemia virus type-1 (HTLV-1) proviral load in HTLV-1-positive patients with rheumatoid arthritis: Baseline data in a single center cohort study. Issue 3 (3rd May 2020) - Eguchi, Katsumi; Iwanaga, Masako; Terada, Kaoru; Aramaki, Toshiyuki; Tuji, Yoshiko; Kurushima, Shouta; Kojima, Kanako; Arima, Kazuhiko; Iwamoto, Naoki; Ichinose, Kunihiko; Kawakami, Atushi; Hirakata, Naoyuki; et al.
Abstract: Objective: Recently, Human T-cell leukemia virus type-1 proviral load (HTLV-1 PVL) has been evaluated as an important predictor of adult T-cell leukemia/lymphoma (ATL) in HTLV-1 carriers. We aimed to evaluate whether HTLV-1 PVL is also important for the development of ATL among HTLV-1-positive patients with rheumatoid arthritis (RA). Methods: We established a cohort of 82 HTLV-1-positive RA patients between 2017 and 2018. Of those, 27 (32.9%) were treated with biological disease-modifying anti-rheumatic drugs (bDMARDs) with/without methotrexate. We measured HTLV-1 PVL in peripheral blood mononuclear cells (PBMCs) at study entry and compared the value by clinical status and treatment options. Results: The median PVL for all was 9.6 copies per 1000 PBMCs without sex difference (male 17.2 and female 8.6; p = .24). The median PVL was significantly higher for patient's comorbid bronchiectasis, malignancies, and opportunistic infectious diseases, compared with patients without comorbidity. There were no significant differences in PVL levels among types of bDMARDs, although the level was tended to be higher for patients treated with JAK inhibitor. Conclusions: HTLV-1 seropositive RA patients comorbid for any diseases having higher HTLV-1 PVLs will be a higher risk for developing ATL. Careful follow-up of these patients is necessary to detect ATL development.